Development of Assemblr Edu-Assisted Augmented Reality Learning Media on Ecosystem Material for Fifth Grade Elementary Students - Lutfiah Azizah; Zaka Hadikusuma Ramadan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
The present study discusses the limited use of technology-based learning media in Natural and Social Sciences (IPAS) instruction at SDN 17 Pekanbaru, where the abstract concept of ecosystems was difficult for fifth-grade students to understand through conventional methods. This research aims to develop and assess the validity and user responses to augmented reality (AR) learning media supported by Assemblr Edu within the materials ecosystem for fifth-grade students. The study employs a research and development (R&D) approach using the ADDIE model, focusing on the Analysis, Design, and Development stages. Data were collected through interviews and questionnaires and analyzed using a percentage formula based on a five-point Likert scale. Validation involves media, material, and language experts, while practicality is assessed through teacher and student responses (n = 7). The results reveal that the media obtained average validity scores of 93.75% (media), 91.76% (material), and 89.44% (language), all in the very valid category, with an overall validity of 91.65%. The teacher response reached 85.33% (very practical), and the average student response reached 83.67% (very interesting). These findings indicate that the developed AR media is valid and practical for supporting ecosystem learning in elementary school and can serve as an alternative technology-based medium for teachers. The novelty of this study lies in developing Assemblr Edu-assisted AR specifically for ecosystem (food-chain) material at the fifth-grade level, an emphasis rarely addressed in prior AR studies that mostly targeted other science topics or focused only on motivation; the study thus contributes a validated, ready-to-use AR medium as a reference for developing technology-based science learning.